Importance of early transfer to higher levels of in-patient care – an experience from a lower-middle-income country - Jibril, Huzefa; Syed Ahsan Ali; Awan, Safia; Tariq, Muhammed (Journal of the Pakistan Medical Association, 2025)
Objective: To ascertain the frequency of hospitalised internal medicine patients requiring escalation to a higher level of care, and in-hospital mortality in such cases. Method: The prospective, observational study was conducted from September 1 to October 15, 2021 at a tertiary care hospital in Karachi, and comprised adult patients of either gender admitted to the internal medicine general wards and high dependency units. Data was collected prospectively using a proforma. Data was analysed using SPSS 23. Results: Of the 837 patients admitted, 617(73.7%) were included. There were 310(50.2%) females and 307(49.8%) males with mean age 52.2±18.8 years. The most common comorbidity was hypertension 288(46.7%). Of the 617 patients, 51(8.3%) required escalation to a higher level of care. Escalation to the intensive care unit and high dependency unit occurred in 19(37.3%) and 32(62.7%) patients, respectively. In-hospital mortality among patients who required escalation to the intensive care unit was 52.6%. In instances where the escalation was required within 48 hours of admission, in-hospital mortality was 8.3% (2/24), whereas, it was 40.7% (11/27) in cases when it was initiated beyond 48 hours of admission (p=0.010). The median length of hospital stay was also significantly lower when the escalation was initiated within 48 hours of admission 5 days (interquartile range: 4-7 days) compared to when it was delayed 13 days (interquartile range: 6-19 days) (p<0.001). The principal discharge diagnosis of sepsis was significantly associated with escalation to a higher level of care (p<0.001) and in-hospital mortality (p<0.001). Conclusions: Initiation of escalation to higher levels of care within 48 hours of admission was found to be associated with reduced in-hospital mortality and length of hospital stay. Key Words: Critical Illness, Intensive care units, Emergency medical service.